Kontribusi Kepercayaan Diri, Kecemasan dan Konsentrasi Terhadap Atlet Bola Basket - Agustina, Wilda; Sulaiman, Sulaiman; Yudha, Donny Wira (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research was conducted to determine the contribution of self-confidence, anxiety and concentration to the performance of Padangsidimpuan basketball athletes. This study uses a quantitative approach. The population was 130 athletes, after sampling using proportional sampling technique, 72 athletes were obtained. The instruments used are questionnaires, grid concentration tests and FIBA Livestats. The data analysis technique uses multiple linear regression analysis. The results showed that there was a significant contribution of self-confidence to the performance of basketball athletes (F count = 67.989, and p value = 0.00) of 49.3%, anxiety to the performance of basketball athletes (F count = 45.042 and p value = 0, 00) of 39.2%, concentration on performance (F count = 57.925 and p value = 0.00) 45%, and the contribution of self-confidence, anxiety and concentration together with performance (F count = 29.927 with p value = 0 .00) is 56.9%. The conclusion of this research shows that:Self-confidence makes a positive contribution to the performance of Padangsidimpuan basketball athletes; Anxiety makes a negative contribution to the performance of Padangsidimpuan basketball athletes; Concentration makes a positive contribution to the performance of Padangsidimpuan basketball athletes; There is a contribution between self-confidence, anxiety and concentration together on the performance of athletes in the city of Padangsidimpuan. Keyword : Anxiety, Confidence, Concentration, Performance